2011
DOI: 10.1158/1535-7163.mct-10-0707
|View full text |Cite
|
Sign up to set email alerts
|

E7080 Suppresses Hematogenous Multiple Organ Metastases of Lung Cancer Cells with Nonmutated Epidermal Growth Factor Receptor

Abstract: While epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors improve the prognosis of patients with EGFR mutant lung cancer, the prognosis of patients with nonmutant EGFR lung cancer, especially those with metastases, is still extremely poor. We have assessed the therapeutic efficacy of E7080, an orally available inhibitor of multiple tyrosine kinases including VEGF receptor 2 (VEGFR-2) and VEGFR-3, in experimental multiple organ metastasis of lung cancer cell lines without EGFR mutations. E7080 ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…Note that these cells were not pretreated with EGF or any other NFκB activator. A549, OVCAR3, H1048, and SW1271 cells have wild-type EGFR (27)(28)(29)(30), whereas HCC827 cells carry an activating EGFR mutation (31). As expected, erlotinib inhibits EGFR phosphorylation in all of these cells and, importantly, it also decreases greatly the phosphorylation of IκB, within 2-3 h (Fig.…”
Section: Egfr Mediates Nfκb Activation In Several Cancer Cell Linessupporting
confidence: 70%
“…Note that these cells were not pretreated with EGF or any other NFκB activator. A549, OVCAR3, H1048, and SW1271 cells have wild-type EGFR (27)(28)(29)(30), whereas HCC827 cells carry an activating EGFR mutation (31). As expected, erlotinib inhibits EGFR phosphorylation in all of these cells and, importantly, it also decreases greatly the phosphorylation of IκB, within 2-3 h (Fig.…”
Section: Egfr Mediates Nfκb Activation In Several Cancer Cell Linessupporting
confidence: 70%
“…In this model, SBC-3 and H1048 cells expressing high levels of Dll4 metastasized to the liver, kidney, bone, and lymph node (17,18). We observed that SBC-3-Dll4-Fc and H1048-Dll4-Fc cells produced significantly fewer numbers of metastatic nodules in the liver compared with the control cells ( Table 1).…”
Section: Dll4-fc Suppresses Liver Metastasis Of Sclc Cells Expressingmentioning
confidence: 73%
“…Two days later, the mice were inoculated with SBC-3, H1048, or SBC-5 cells into the tail vein (16)(17)(18). The mice were sacrificed humanely under anesthesia, and the major organs were then removed and weighed and the number of metastatic nodules on the surface of the organs was counted.…”
Section: In Vivo Metastasis Modelsmentioning
confidence: 99%
“…VEGF plays an important role in tumor growth and is involved in angiogenesis, in relation to the development of metastasis. Lenvatinib showed potent antitumor efficacy with a broad spectrum of human tumor xenograft models, on the basis of inhibitory activity toward VEGF receptors 2 and 3 (Matsui et al, 2008a;Ikuta et al, 2009;Ogino et al, 2011).…”
Section: Introductionmentioning
confidence: 99%